Attitudes toward the elderly among young family physicians in Turkey - Tugba Caliskan; Candan Kendir; Nil Tekin; Mehtap Kartal (Journal of Family Medicine and Primary Care, 2018)
Introduction: General practitioners'(GPs) role is important as they are easily accessible especially for elderly. Young GPs need to improve their attitudes toward the elderly so that they can be a part of solution for health problems of elderly in the future. The aim of this study is to determine attitudes of young GPs toward elderly by the University of California at Los Angeles Geriatrics Attitude Scale (UCLA-GAS). Methods: It is a cross-sectional study performed with questionnaires including UCLA-GAS. The study population was 260 young doctors (GP residents and GPs in their first 5 years after qualification). Statistical evaluation of the data included percentage, mean, and Kolmogorov–Smirnov test and analysis of variance test. Results: Of the participants, 58.1% (n = 151) were women, 35.4% (n = 94) of them were GPs, and the remaining were GP residents. The mean age was 31.30 ± 5.40 years (range = 24–55 years). The mean score of UCLA-GAS was 46.85 ± 5.63 (range = 30–61). Participants ≤30 years of age had significantly higher scores (47.70 ± 5.99) than age above 30 years (45.68 ± 4.89) (P = 0.003). There was no statistically significant difference between GP residents and GPs (P = 0.989) and between participants who had rotation in elderly healthcare service (n = 63) or not (n = 197) (P = 0.383). However, as the duration of work increased, the score of UCLA-GAS decreased significantly (r = −0.216, P < 0.001). Conclusion: Young doctors who were interested in elderly showed more positive attitude as expected. However, the ones who were older and worked longer had less positive attitude. It seems important to understand and prevent this unfavourable attitude with formal education system about elderly healthcare during residency.